Durkheim and Hubert in Brazil - Maia, João Marcelo Ehlert (Serendipities. Journal for the Sociology and History of the Social Sciences, 2018)
Book review of: Benthien, Rafael, Miguel Palmeira and Rodrigo Turin (Eds.). 2016. Hubert, Henri, Estudo Sumário da Representação do Tempo na Religião e na Magia. São Paulo: Editora da Universidade de São Paulo (=Biblioteca Durkheimiana vol. 2). 160 pp. Bilingual: Brazil Portugese and French. ISBN: 978-8-531-41596-8 Price: Por R$ 28,80 Consolim, Márcia, Márcio de Oliveira e Raquel Weiss (Eds.). 2017. Émile Durkheim, O Individualismo e os Intelectuais. São Paulo: Editora da Universidade de São Paulo (=Biblioteca Durkheimiana vol. 1) 192 pp. Bilingual: Brazil Portugese and French. ISBN: 978-8-531-41595-1 Price: Por R$ 25,60